Molecular identification of Sarcocystis aucheniae as the macrocyst-forming parasite of llamas - Carletti, Tamara (2013)
The domestic South American camelids (SACs), llama (Lama glama) and alpaca (Lama paco), are frequently found to be infected with Sarcocystis parasites. Infections give rise in skeletal muscle to macroscopic cysts (1–5 mm long) that resemble rice seeds, each containing several million living bradyzoites. The finding of cysts prevents commercialization of SAC meat, an important source of income for rural families in the Andean flatlands. Thus, development of diagnostic methods to facilitate the control of these infections is highly desirable, and the first step to this end is the unequivocal species identification of the causative agent. Based on the cyst form and size, the infecting parasite has been described as Sarcocystis aucheniae; however, this traditional approach is not reliable as similar cysts may contain different species. To date, molecular identification has been done for a single isolate of S. aucheniae from an alpaca in Australia. In order to verify the identity of the species present in SACs of South America, the complete 18S rRNA gene was PCR-amplified and sequenced from macrocyst DNA obtained from three llamas of the Andean flatlands. A phylogenetic Bayesian analysis was carried out using the analyzed and available 18S rRNA sequences of Sarcocystis spp. In the constructed tree, all of the new 18S rRNA gene sequences segregated in a single clade together with the 18S rRNA gene sequence reported from an alpaca in Australia, demonstrating that the isolated parasite is S. aucheniae, and that this parasite indiscriminately infects both domestic SACs. This work represents the first molecular identification of the causative agent of SAC sarcocystiosis in South America, and can contribute to the development of control methods for this neglected parasitosis.